Focal Therapy, Differential Therapy, and Radiation Treatment for Prostate Cancer - Anudh K. Jain; Ronald D. Ennis (Advances in Urology)
Focal and differential therapy represent an approach to improve the therapeutic ratio of prostate cancer treatments. This concept is a shift from treating the whole gland to intensely treating the portion of the gland that contains significant tumor. However, there are many challenges in the move towards focal approaches. Defining which patients are suitable candidates for focal therapy approaches is an area of significant controversy, and it is likely that additional data from imaging or detailed biopsy methods is needed in addition to traditional risk factors. A number of methods have been suggested, and imaging with multiparametric MRI and transperineal template mapping biopsy have shown promise. The approach of differential therapy where the entire prostate is treated to a lower intensity and the tumor areas to high intensity is also discussed in detail. Radiation therapy is a well suited modality for the delivery of differential therapy. Data in the literature using external beam radiation, high dose rate brachytherapy, and low-dose rate brachytherapy for differential therapy are reviewed. Preliminary results are encouraging, and larger studies and randomized controlled trials are needed to validate this approach.